Chart showing Mr. Leigh Smith's track to Franz Josef Land and boat journey to Novaya Zemlya in 1881-1882 / H. Sharbau, del. - Sharbau, H. (Henry) (Royal Geographical Society (Great Britain), 1883)
Relief shown by hachures. Color 1:6,000,000